Toxicity Test of Hydrocarbon Exposure on Lepironia articulate in Phytoremediation Process - Al-Sbani, Nadya Hussin; Sheikh Abdullah, Siti Rozaimah; Idris, Mushrifah; Hasan, Hassimi Abu; Jehawi, Omar Hamed; Ismail, Nur 'Izzati (Asian Journal of Chemistry, 2015)
The green technology became the world’s attention including the use of plants (phytoremediation) to remove and degrade the contaminants. Phytoremediation need to identify these plants and its ability to resist toxicity of contaminants before a full-scale system can be installed to ensure that the remedy is effective by selected plants. The aim of this study is to investigate the ability of a native plant in Malaysia (Lepironia articulate) to survive when exposed to different diesel concentrations (0, 5, 10, 20, 30, 35 and 40 mL diesel/L water). This was done with two adopted flow systems, free surface (FSF) and sub-surface flow (SSF) to observe in which system the plant can survive and tolerate diesel better. At the end of diesel exposure, the result indicated that the plant growth in sub-surface flow was better compared to the free surface system. It was observed that 33 % of the plants wilted after exposure to diesel concentrations of 30 and 35 mL/L and 66.7 % withered in 40 mL/L diesel concentration in sub-surface flow. While in free surface, 66.7 % of plants wilted at 10 and 20 mL/L and 100 % of plants wilted at 30, 35 and 40 mL/L. Hence, L. articulate had better growth when exposed to diesel in a sub-surface flow system.